Same Surgeon: Different Centre Equals Differing Lymph Node Harvest following Colorectal Cancer Resection. (14th February 2011) - Evans, M. D.; Robinson, S.; Badiani, S.; Rees, A.; Stamatakis, J. D.; Karandikar, S. S.; Langman, G.
Abstract : Introduction . The aim of this study was to examine the effect of surgeon relocation on lymph node (LN) retrieval in colorectal cancer (CRC) resection. Methods . The study population was 213 consecutive patients undergoing CRC resection by a single surgeon, at two units: unit one 110 operations (2002–2005) and unit two 103 (2005–2009). LN yields and case mix were compared. Results . Median LN harvests were significantly different between the two centres: unit 1: 13 nodes/patient and unit 2: 22 nodes/patient (P < .001 ). In unit one 42% of cases were LN positive and in unit two 48% (P = .398 ). There was no difference in case mix. Multivariate analysis identified unit (P < .001 ) and pathologist (P = .007 ) as independent predictors of harvest. Conclusions . A surgeon moving units can experience significantly different LN yield following CRC resection. Both units comply with national standards, but the "surgeon's results" at the two units appear to be pathologist dependent. This has implications for nodal harvest as a surrogate marker of surgical quality.